Abordagens de violência contra a mulher em telenovelas brasileiras: uma análise feminista de discurso - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
This study proposes a Feminist Discourse Analysis that investigates the imposition of violence against women in brazilian telenovelas, exploring how this violence manifests itself, how it affects the victims, and how the interdiscourse of telenovelas with the legal aspects of combating gender-based violence develops.. Using the television dramas Mulheres Apaixonadas and A Regra do Jogo as the objects of study, the research aims to understand how these media narratives construct and perpetuate representations of gender-based violence, as well as examine their potential to raise awareness and promote consciousness regarding issues related to violence and women's rights. In this regard, the specific objectives are defined: (i) to comprehend, through feminist theories, how brazilian telenovelas represent violence against women; (ii) to observe how the representation depicted in telenovelas engages with the feminist struggles of brazilian and latin american women; (iii) to observe the transformations this dialogue has undergone over time. The theoretical framework is based on the works of Mauro Alencar (2002), Esther Hamburguer (2005) — to critically rethink the trajectory of Brazilian soap opera construction; Mary Del Priore (1993), Miriam Pillar Grossi (1994), Marcela Lagarde (2003, 2012), Heleieth Saffioti (2015) — to discuss the issue of violence against women in Latin America and the world; Judith Butler (2003), Sandra Harding (2019), Amanda Diniz Vallada and Joana Plaza Pinto (2021), Isadora Costa Mendes and Lúcia Freitas (2017) — to discuss discursive studies from a feminist perspective. The research conclusions have shown that brazilian telenovelas present approaches to violence against women that encourage debates and reflections on the subject. However, almost twenty years later, these plots have made little progress, especially when compared to the achievements made by feminist movements, particularly in terms of representing the legal aspects of combating gender-based violence.
Representations of violence against women in brazilian telenovelas: a feminist discourse analysis
Keywords: Novelas brasileiras - Análise Feminista de Discurso; Novelas brasileiras - Violência de gênero; Brazilian telenovelas - Feminist discourse analysis; Brazilian telenovelas - Gender-based violence; LINGUISTICA::SOCIOLINGUISTICA E DIALETOLOGIA